2020
DOI: 10.1128/jvi.01233-19
|View full text |Cite
|
Sign up to set email alerts
|

The Capsid Protein of Semliki Forest Virus Antagonizes RNA Interference in Mammalian Cells

Abstract: RNA interference (RNAi) is a conserved antiviral immune defense in eukaryotes, and numerous viruses have been found to encode viral suppressors of RNAi (VSRs) to counteract antiviral RNAi. Alphaviruses are a large group of positive-stranded RNA viruses that maintain their transmission and life cycles in both mosquitoes and mammals. However, there is little knowledge about how alphaviruses antagonize RNAi in both host organisms. In this study, we identified that Semliki Forest virus (SFV) capsid protein can eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…Thus, when VSR is rendered nonexpressing or nonfunctional, the resulting mutant viruses induce abundant vsiRNAs, replicate less efficiently than parental viruses in mESCs, mature murine, monkey, and human cells, and/or newborn mice and are efficiently rescued by knocking out all four Ago genes in mESCs or Dicer gene in human 293T cells ( 10 , 12 15 ). Moreover, ebolavirus VP35 and the nucleocapsid protein of yellow fever virus ( Flaviviridae ), Semliki Forest virus ( Togaviridae ), and severe acute respiratory syndrome coronavirus (SARS CoV) and SARS CoV-2 also display activities of dsRNA-binding VSRs ( 15 , 17 19 , 64 , 65 ). Together, these findings reveal a new mammalian antiviral response mediated by the RNAi pathway with striking similarities to the siRNA-directed antiviral response characterized extensively in plants and invertebrates ( 7 9 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, when VSR is rendered nonexpressing or nonfunctional, the resulting mutant viruses induce abundant vsiRNAs, replicate less efficiently than parental viruses in mESCs, mature murine, monkey, and human cells, and/or newborn mice and are efficiently rescued by knocking out all four Ago genes in mESCs or Dicer gene in human 293T cells ( 10 , 12 15 ). Moreover, ebolavirus VP35 and the nucleocapsid protein of yellow fever virus ( Flaviviridae ), Semliki Forest virus ( Togaviridae ), and severe acute respiratory syndrome coronavirus (SARS CoV) and SARS CoV-2 also display activities of dsRNA-binding VSRs ( 15 , 17 19 , 64 , 65 ). Together, these findings reveal a new mammalian antiviral response mediated by the RNAi pathway with striking similarities to the siRNA-directed antiviral response characterized extensively in plants and invertebrates ( 7 9 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies show that the RuV capsid forms a disulfide-linked dimer [ 47 ]. Moreover, previous studies showed that homodimerization is critical for VSR’s activity [ 18 , 19 , 20 , 29 , 43 ]; we focused on the key region or residues responsible for the dimerization of the RuV capsid.…”
Section: Resultsmentioning
confidence: 99%
“…The full-length cDNA of the FHV RNA1 and FHV RNA1 ΔB2 was described previously [ 12 ]. For the purification of the MBP fusion capsid protein, its ORF was inserted into the pFastBac-MBP vector [ 43 ]. The EGFP-siRNA (siEGFP) was chemically synthesized by Rui Bo, Guangzhou, China.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations